2015
DOI: 10.4103/0301-4738.176038
|View full text |Cite
|
Sign up to set email alerts
|

A case of giant nodular posterior scleritis mimicking choroidal malignancy

Abstract: To report a case of giant nodular posterior scleritis mimicking a choroidal tumor. A 42-year-old lady with systemic hypertension presented with a 1-week history of unilateral visual loss, pain and redness in her left eye. Examination showed sectoral anterior episcleritis in her left eye as well as a dome-shaped choroidal mass at the inferior-temporal periphery, associated with retinal hemorrhages and subretinal fluid. Systemic evaluation and imaging of the choroidal mass were performed and could not rule out a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Due to its low incidence and variable clinical presentation, the mechanism underlying PS remains unclear and the majority of the research to date has focused instead on characterizing its clinical features, and optimizing diagnosis, treatment, and patient outcome [2][3][4]. Based on the anatomical location, PS presents with a range of clinical features, especially in fundus change, and, therefore, is often misdiagnosed as intraocular inflammation [5], ocular tumors [6], or orbital inflammation [7]; such misdiagnoses [8] increase the likelihood of incurring irreversible visual damage including eventual vision loss. Given the high rates of retinal detachment in PS [4], this condition can be easily misdiagnosed as central serous chorioretinopathy (CSC), which is characterized by retinal detachment in or around the macula.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its low incidence and variable clinical presentation, the mechanism underlying PS remains unclear and the majority of the research to date has focused instead on characterizing its clinical features, and optimizing diagnosis, treatment, and patient outcome [2][3][4]. Based on the anatomical location, PS presents with a range of clinical features, especially in fundus change, and, therefore, is often misdiagnosed as intraocular inflammation [5], ocular tumors [6], or orbital inflammation [7]; such misdiagnoses [8] increase the likelihood of incurring irreversible visual damage including eventual vision loss. Given the high rates of retinal detachment in PS [4], this condition can be easily misdiagnosed as central serous chorioretinopathy (CSC), which is characterized by retinal detachment in or around the macula.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is sometimes difficult to distinguish between the two, and we usually hesitate to increase the amount of corticosteroid administered in such cases. Liu et al reported that a patient with a lesion similar to the one in our case improved with a nonsteroidal anti-inflammatory drug (NSAID) [ 11 ]. Since it is thought that NSAIDs produce fewer side effects than corticosteroids, it might also be better to try NSAID administration in our present case.…”
Section: Discussionmentioning
confidence: 93%
“…[ 7 ] A trial of corticosteroid or non-steroidal anti-inflammatory drugs (NSAIDs) can differentiate masquerading scleritis of uveal melanoma from posterior scleritis with likelihood of resolution of mass following treatment with the latter. [ 8 9 ] Our patient was treated with topical and systemic steroid, which improved the secondary scleritis and exudative retinal detachment. Though it did not shrink the choroidal mass, the tumor appeared more solid and well organized, supporting the diagnosis of choroidal melanoma.…”
Section: Discussionmentioning
confidence: 97%